Frictional heating lubrication for submarine landslide - Wen-yau Chen; Ray-yeng Yang; Hwung-hweng Hwung (Terrestrial, Atmospheric and Oceanic Sciences, 2018)

(untitled)
Given a large block of fine-grained sediment that overlies a 1° continental slope, if the entire sediment deposit is shaken by an earthquake to slide down the slope with an initial velocity (referred to as "submarine landslide" hereinafter), our block model showed that the whole deposit can continuously slide downslope with the “help” of basal frictional heating. In theory, basal Coulomb friction can generate a thermal internal energy in the basal shear zone of landslides (called "frictional heating"), the increasing temperature activating two mechanisms. One mainly decreases the Terzaghi effective normal stress of the landslides and the other decreases the Coulomb friction coefficient. Combining these two mechanisms can effectively decrease the basal frictional resistance of the landslides increasing the mobility of the landslides on gentle slopes (entitled as "frictional heating lubrication"). As shown in our calculations, frictional heating increases with the increase of the initial downslope velocity but decreases with the increase of the shear zone thickness.